A Multilayer Film Based Selective Thermal Emitter for Infrared Stealth Technology. Issue 23 (21st October 2018) - Peng, Liang; Liu, Dongqing; Cheng, Haifeng; Zhou, Shen; Zu, Mei
Abstract: Engineering the radiation characteristics for the design of selective thermal emitters has been a hot topic for decades and is of great value in the fields of thermophotovoltaic systems, radiative cooling, and infrared stealth. In this paper, a Ag/Ge multilayer film based selective emitter for infrared stealth is demonstrated using an ultrathin metal film and impedance matching to tune the radiation characteristics. Herein, a novel approach for infrared stealth that relies on the combination of emissivity (ε) reduction in the atmospheric windows (3–5 and 8–14 µm) and radiative cooling in a nonatmospheric window (5–8 µm) is proposed. The fabricated selective emitter has low emissivity (ε3‐5 µm = 0.18; ε8‐14 µm = 0.31) in the atmospheric windows for infrared "invisibility" and high emissivity (ε5‐8 µm = 0.82) outside the atmospheric window for radiative cooling and functions from ambient temperature to 200 °C. Compared with low‐emissivity materials, the selective emitter exhibits higher radiative cooling efficiency in vacuum and practical environments and presents lower apparent temperatures on infrared cameras. Moreover, the proposed selective emitter, with a planar and simple structure, is scalable, allowing flexible large‐area fabrication. The work demonstrates that selective emissive materials have promising applications in infrared stealth technology. Abstract : A multilayer film based selective emitter for infrared stealth is proposed. The selective emitter exhibits remarkable selective emission properties: low emissivity in the atmospheric windows and high emissivity in the 5–8 µm window. Compared with low‐emissivity materials, the selective emitter exhibits better performance in radiative cooling and in infrared stealth. The work shows that selective emissive materials have promising application prospects.